Nasionalisme dan Pancasila Perspektif Sukarno - Wendy Anugrah Octavian; Puspa Dianti (Departement of Mathematics Education, 2023)
This paper intends to find out various things that are very important about nationalism, Pancasila in Sukarno's perspective. The method used in this research is descriptive research method with a qualitative approach. The descriptive method can be interpreted as an effort made to reveal the situation and provide an objective description of the object under study. Data collection techniques from this study used literature studies. Researchers interpret the meaning of existing theories and articles. The result of this study is that nationalism or socio-nationalism according to Sukarno's view is nationalism that is humanist, originates from the Indonesian people themselves, not from other nations, and is more concerned with the nation and state than individual or group interests. The basic values of Pancasila put forward by Sukarno are the result of excavations from religion, culture, customs that exist in the life of the Indonesian nation and have been applied in the daily life of Indonesian society. Sukarno placed the precepts of God at the base or final sequence meaning that God was the initial basic foundation for the creation or formation of the other precepts, not positioning God below.